Effect of carob (Ceratonia siliqua) on growth parameters and viability of local Algerian rabbit populations (Oryctolagus cuniculus) - Meziane, R; Boughris, F; Boughris, M; Boudib, FZ; Khenissa, R (Journal of the Hellenic Veterinary Medical Society, 2024)
The objective of this study is to evaluate the effect of incorporating different levels of carob on carcass quality and the viability of the local rabbit in eastern Algeria. Carob diets with 3.5 kg/T, 5 kg/T, and 100% carob were distributed to 3 groups of kids from the local population, from weaning at 28 days to slaughter at the age of 110 days. The statistical results show the effect of using carob and also with an incorporation rate of 3.5 kg/T on the live weight of the rabbits and led to a decrease in feed conversion ratio, good feed efficiency, and feeding costs. The highest ADG (28-108 days) and final weight at 108 days are 25.82 g/day, and 1328.37 g respectively. The best performing CI was 3.32, obtained during the growing period for a rabbit weaned at 28 days (Group 1) receiving carob supplementation. As a result, the health risk index, or "HRI," was higher for rabbits in the G1 and G2 whole fattening periods (28-35 and 35-49 days, respectively), and then decreased for the remainder of the period. Mortality and morbidity measurements do not indicate any significant effect of carob use on the health status of rabbits (P < 0.05).The results of this work showed that the supplementation of carob improves the growth performance and dressing yield of local rabbits.